Accuracy of the Application of 3-Dimensional Printing Models in Orbital Blowout Fractures—A Preliminary Study. (March 2022) - Ma, Chun-Yu; Wang, Tien-Hsiang; Yu, Wen-Chan; Shih, Yu-Chung; Lin, Chih-Hsun; Perng, Cherng-Kang; Ma, Hsu; Wang, Shyh-Jen; Chen, Wei-Ming; Chen, Ching-En
Abstract : Background: Application of 3-dimensional (3D) printing technology has grown in the medical field over the past 2 decades. In managing orbital blowout fractures, 3D printed models can be used as intraoperative navigators and could shorten the operational time by facilitating prebending or shaping of the mesh preoperatively. However, a comparison of the accuracy of computed tomography (CT) images and printed 3D models is lacking. Material and Methods: This is a single-center retrospective study. Patients with unilateral orbital blowout fracture and signed up for customized 3D printing model were included. Reference points for the 2D distance were defined (intersupraorbital notch distance, transverse horizontal, sagittal vertical, and anteroposterior axes for orbital cavity) and measured directly on 3D printing models and on corresponding CT images. The difference and correlation analysis were conducted. Results: In total, 9 patients were reviewed from June 2017 to December 2020. The mean difference in the intersupraorbital notch measurement between the 2 modules was −0.14 mm ( P = 0.67). The mean difference in the distance measured from the modules in the horizontal, vertical, and anteroposterior axes of the traumatic orbits was 0.06 mm ( P = 0.85), −0.23 mm ( P = 0.47), and 0.51 mm ( P = 0.32), whereas that of the unaffected orbits was 0.16 mm ( P = 0.44), 0.34 mm ( P = 0.24), and 0.1 mm ( P = 0.88), respectively. Although 2D parameter differences (<1 mm) between 3D printing models and CT images were discovered, they were not statistically significant. Conclusions: Three-dimensional printing models showed high identity and correlation to CT image. Therefore, personalized models might be a reliable tool of virtual surgery or as a guide in realistic surgical scenarios for orbital blowout fractures.